Al-Balqa Applied University Intermediate Colleges Commitment to Exclusive Standards of Technical Education - Mohareb Ali Alsmadi (University of Science and Technology, Yemen, 2016)
Abstract: This study investigated Al-Balqa Applied University Intermediate Colleges Commitment to Exclusive Standards of Technical Education. The study involved a randomly chosen sample of 123 members of the teaching staff in three colleges (The technological Engineering College, El-Husun University College and Ajloun University College). The study tool consisted of sixty items related to six variables (leadership, organizational culture, planning, curricula, teaching technology, scientific research, community service and development). The statistical analysis showed that the responses were at the average level and there were no significant differences (α =0.05) in the evaluations of the members of the study of the colleges commitment to the Exclusive Standards of Technical Education, based on the study variables (college, academic degree, teaching experience and specialty. It was  recommended that an international electronic data-base should be provided,  and that Exclusive Standards of Technical Education should be adopted to evaluate the quality of teaching at technical colleges.